The development of strategic HRM: reflections on a 30-year journey. (2nd January 2018) - Boxall, Peter
ABSTRACT: Approximately 30 years since my paper with Peter Dowling on 'Human Resource Management and the Industrial Relations Tradition' was published in Labour and Industry, this paper reflects on how the academic literature on Human Resource Management (HRM), particularly strategic HRM, has developed. Starting with a reprise of the claims in the original article, it offers an overview of the state of the field and concludes that there is a mixed report card for the last 30 years. There is clearly a need to more carefully theorise the economic motives of the firm and to understand the history and variety of employer behaviour in its diverse context. Hard work continues to be required in integrating theories from different disciplines and academics need to be open to research methods beyond their own personal preference. However, strategic HRM has become a more balanced subject, which embraces both sides of the employment relationship: employee well-being and organisational performance. While improving the rigour of our research methods is going to be important in the next 30 years, research in strategic HRM should also focus on making a better contribution to societal debates about the opportunities and problems of employment relations.